2002
DOI: 10.1523/jneurosci.22-10-04025.2002
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Sensory Innervation of the Olfactory Bulb in Neuropilin-2 Mutant Mice

Abstract: The mammalian olfactory system consists of two anatomically segregated structures, the main olfactory system and the vomeronasal system, which each detect distinct types of chemical stimuli in the environment. During development, sensory neurons establish precise axonal connections with their respective targets within the olfactory bulb. The specificity of the odorant or vomeronasal receptor expressed by the sensory neuron is crucial in this process, yet it is less clear which of the more conventional axon gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
159
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(170 citation statements)
references
References 52 publications
9
159
1
1
Order By: Relevance
“…Members of the secreted semaphorin (Sema) family and their receptors, the neuropilins, have been implicated in the development of OSN projections. (de Castro et al, 1999;Pasterkamp et al, 1999;Renzi et al, 2000;Schwarting et al, 2000;Walz et al, 2002;Cloutier et al, 2004;Schwarting et al, 2004). Indeed, Sema3A is required for appropriate medial to lateral targeting of OSN axons (Schwarting et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the secreted semaphorin (Sema) family and their receptors, the neuropilins, have been implicated in the development of OSN projections. (de Castro et al, 1999;Pasterkamp et al, 1999;Renzi et al, 2000;Schwarting et al, 2000;Walz et al, 2002;Cloutier et al, 2004;Schwarting et al, 2004). Indeed, Sema3A is required for appropriate medial to lateral targeting of OSN axons (Schwarting et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are five other members of the class 3 family of semaphorins (Semaphorin Nomenclature Committee, 1999). Between them, they regulate the formation of neuronal networks in many regions of the CNS, including the hippocampus, cerebral cortex, and olfactory system (Chedotal et al, 1998;Polleux et al, 1998;Schwarting et al, 2000;Pozas et al, 2001;Cloutier et al, 2002;Walz et al, 2002;Taniguchi et al, 2003). In addition to directing growth cone movements, they regulate the migration of cells, including neural crest and neuronal progenitor cells (Song et al, 1998;Eickholt et al, 1999;Bagnard et al, 2001;Kawasaki et al, 2002) and, thus, may play a role in shaping anatomic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The screening of molecules that were up-regulated in the CMS-induced cells, and down-regulated in the CMS-inhibited cells, revealed Nrp2 as a candidate. Interestingly, analysis of the heterozygous Nrp2-Δ mouse brain ( +/− ), in which tauGFP was knocked in into the Nrp2 locus (19), revealed that the pattern of Nrp2 expression was similar to that of COUP-TFII (Fig. 6).…”
Section: Nrp2 Is Preferentially Expressed In the Cms And Functions As Amentioning
confidence: 97%